Legal protection of the rights of workers to the termination of working relationship to the bankcruptcy company - Hasan, Hasbi (2017)
Purpose - Ensuring the rights of laborers both materially, socially, psychologically, and law becomes a complex issue happening in the world in general, including Indonesia.Starting from the termination of employment impact on the criminality, the number of unemployed, welfare, and equality of employment opportunities in the midst of competition and industry development continues to change.Although there has been a work agreement with the company with the purpose of work and corporate life balance but always the victims of the sufferer are the workers or workers. Not to mention, do not understand and the power of laborers in doing lawsuit status of their legal rights.On the other hand, this problem is contrary to the protection of workers’ rights guaranteed in the life of the nation and the state (Constitution) and the Law No.13 on Employment as a guide for workers, and Law No.37 of 2004 on Bankruptcy and Suspension of Payment Obligations.Methodology - This paper uses normative legal research method. Primary data sources are secondary legal materials, and primary legal materials where the primary data as supporting secondary legal data material.The process of data analysis using qualitative juridical analysis method.Findings - Legal certainty of workers after the expiry of employment relationship with company, in case the company declared bankrupt or liquidation pursuant to regulation of Law No.13 Year 2003 on Manpower.A form of legal protection that workers can exercise against unmet rights ie, workers through existing legal means.Workers as privileged creditors may pursue legal remedies ie lawsuits through industrial relations courts relating to employment or other claims.